The 7th hunt - Cohen, J D; Bailey, Imogen, 1977-; Stojanovski, Jason; Charleston, Matthew (CineGear Productions : Coherent Productions, 2009)
For Gothic Callie, her deaf sister Ariel, computer nerd Chris, popular Sarah, and misogynist Ricky, their evening plans are about to be re-written. Taken to an abandoned military training school, they finds themselves the target of 5 sadistic killers, each with their own unique and different style of killing. They fight for their lives against sociopaths who know their environment intimately, becoming increasingly outnumbered as their friends are killed. --